1986
DOI: 10.1200/jco.1986.4.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Combination intraventricular chemotherapy for meningeal neoplasia.

Abstract: Twenty two patients with meningeal neoplasia were treated with biweekly combination intraventricular chemotherapy using methotrexate, cytosine arabinoside, and thiotepa. Patients with the following malignancies were included: breast cancer, ten patients; lung cancer, seven; non-Hodgkin's lymphoma, two; malignant melanoma, one; transitional cell carcinoma of the bladder, one; and malignant glioma, one. Eight of 22 patients (36%) had a Karnofsky performance status of less than 50%. Eleven of 22 patients received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(48 citation statements)
references
References 20 publications
1
47
0
Order By: Relevance
“…However, it is noted that most series exclude patients that are too sick to receive any treatment, which may be up to one third of patients with NM [64]. Three agents are routinely used: methotrexate, cytarabine (including liposomal cytarabine or DepoCyt [Enzon Phar- [65][66][67]. Table 1 outlines the randomized clinical trials conducted for NM whereas Table 2 is an outline of the common treatment regimens for intra-CSF chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
“…However, it is noted that most series exclude patients that are too sick to receive any treatment, which may be up to one third of patients with NM [64]. Three agents are routinely used: methotrexate, cytarabine (including liposomal cytarabine or DepoCyt [Enzon Phar- [65][66][67]. Table 1 outlines the randomized clinical trials conducted for NM whereas Table 2 is an outline of the common treatment regimens for intra-CSF chemotherapy.…”
Section: Chemotherapymentioning
confidence: 99%
“…However, only a few anticancer drugs, including methotrexate, cytosine arabinoside, triethylene thiophosphoramide, and 5-fluoro-2V -deoxyuridine (FdUrd), can be injected intrathecally (1)(2)(3)(4)(5). The intrathecal administration of these anticancer agents achieves a therapeutic efficacy of 40% to 70%, and leads to temporary cancer regression for a short period in some cases, but, in other many cases, fails to improve the patient's performance status.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluated 61 patients with LC (10 with lung cancer) and found a better median time to neurological progression for intrathecal liposomal cytarabine over intrathecal methotrexate (58 vs (82). However, other trials did not demonstrate superiority of intrathecal combination therapy over single-agent (83,84), therefore the role of a combination therapy remains uncertain. In addition to the most frequently used drugs, intrathecal administration of gemcitabine (85) or etoposide (86) has resulted in clinical activity in some case reports.…”
Section: Chemotherapy As Salvage Treatment For Progressive Bmsmentioning
confidence: 99%